Evolutionary Adaptations in Pseudonaja Textilis Venom Factor X Induce Zymogen Activity and Resistance to the Intrinsic Tenase Complex - Schreuder, Mark; Poenou, Geraldine; Strijbis, Viola J. F.; Cheung, Ka Lei; Reitsma, Pieter H.; Bos, Mettine H. A. (Thrombosis and Haemostasis, 2020)
The venom of the Australian snake Pseudonaja textilis comprises powerful prothrombin activators consisting of factor X (v-ptFX)- and factor V-like proteins. While all vertebrate liver-expressed factor X (FX) homologs, including that of P. textilis, comprise an activation peptide of approximately 45 to 65 residues, the activation peptide of v-ptFX is significantly shortened to 27 residues. In this study, we demonstrate that exchanging the human FX activation peptide for the snake venom ortholog impedes proteolytic cleavage by the intrinsic factor VIIIa–factor IXa tenase complex. Furthermore, our findings indicate that the human FX activation peptide comprises an essential binding site for the intrinsic tenase complex. Conversely, incorporation of FX into the extrinsic tissue factor–factor VIIa tenase complex is completely dependent on exosite-mediated interactions. Remarkably, the shortened activation peptide allows for factor V-dependent prothrombin conversion while in the zymogen state. This indicates that the active site of FX molecules comprising the v-ptFX activation peptide partially matures upon assembly into a premature prothrombinase complex. Taken together, the shortened activation peptide is one of the remarkable characteristics of v-ptFX that has been modified from its original form, thereby transforming FX into a powerful procoagulant protein. Moreover, these results shed new light on the structural requirements for serine protease activation and indicate that catalytic activity can be obtained without formation of the characteristic Ile16–Asp194 salt bridge via modification of the activation peptide.
Keywords: factor X; serine protease; prothrombinase complex; enzyme precursors; blood protein disorders